Analisis Faktor-Faktor Yang Mempengaruhi Mobilitas Sosial Masyarakat Nelayan di Desa Kelombok Lingga - Romi Aqmal; Suyito; Dzul Hidayatullah (Jurnal Masyarakat Maritim, 2023)
There are many factors that influence the social mobility process of fishermen, both internally and externally, which become incentives or obstacles for fishing communities in carrying out mobility movements both vertically and horizontally. To answer the above problems, this research uses a qualitative descriptive approach, with data collection methods through observation, interviews and documents using the Miles, Huberman and Saldan analysis model, namely through data condensation, data presentation and drawing conclusions. Based on the results of the analysis, it is found that in general the factors driving fishermen's social mobility are influenced by individual factors such as (age, access to health, skills or personal abilities), educational factors (fishermen's education factors, continuing children's education, and better school access), economic factors. (high operational costs, fluctuating income, high living needs,) natural factors (extreme weather, environmental pollution), social situation factors (invitation from relatives or neighbors, new environment, trying new leisure activities, new experiences and luck in other places). Meanwhile, the researchers found that the factors inhibiting social mobility of fishing communities in Kelombok Village were cultural factors, traditional values, race and ethnicity, economic limitations, concerns about adapting to a new environment).